الاتجاهات نحو ريادة الأعمال وعلاقتها بالمتغيرات النفسية لدى طلبة الصف الثاني عشر بمدارس التعليم ما بعد الأساسي في سلطنة عمان - Ma Mari Rashid Ahmed Mohammed (Universiti Sains Islam Malaysia, 2024)
This study examined the level of students’ attitude towards entrepreneurship and the impact of demographic variables (gender, guardian's profession, educational governorate) on the 12th grade of post-primary education in the Sultanate of Oman. The study also analyzes the correlation of students' attitudes toward entrepreneurship with the psychological variables represented in (self-confidence, self-esteem, and achievement motivation). This study was based on the descriptive approach. The study used a sample size (n= 600) from the 12th grade students of post-primary education in the Sultanate of Oman for the academic year 2017/2018 in the provinces of North Batinah, Muscat and Buraimi. The study used a questionnaire consisting of four measures; the level of attitudes towards entrepreneurship, self-confidence, self-esteem, and motivation for achievement. The results of the study showed that the levels of attitudes toward entrepreneurship among students were high. The results also showed that there was no statistically significant effect of gender variable and the guardian's occupation on the level of attitudes toward entrepreneurship among students. The results showed that there is a statistically significant effect of educational province on the level of attitude towards entrepreneurship confined with Muscat and Al-Buraimi provinces, where Al-Buraimi was positively influenced. The results also showed no statistically significant differences between the levels of attitudes toward entrepreneurship among students due to psychological variables (self-confidence, self-esteem, motivation for achievement). The results further showed a high correlation between psychological variables and attitudes toward entrepreneurship in the population in question. The study recommended to conduct studies about psychological, behavioral and personality traits that were not addressed in this study so that as to discover how such variables influence students' attitudes towards entrepreneurship. The study also recommended adopting the results of studies on the skills of entrepreneurship in the behavioral personality traits of entrepreneurs. Among the recommendations of the study is to carry out training programs that contribute to the development of the psychological characteristics of the students, as well as to reconsider encouragement and dissemination of entrepreneurship culture among students at various educational programs’ stages.